Synthesis and Analysis of Experiences in Ecosystem Services - Scarazatti, Bruno; Nogueira Junior, Lauro Rodrigues (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
Considering that the initiatives of payment for environmental services (PES) are already a reality in Brazil, the present work aimed to promote a critical analysis of experiences in ecosystem services, so that new initiatives can take advantage of it to overcome difficulties in the implementation of PES projects and programs. Using systematization methods, ten experiences were synthesized and analyzed (Oásis Project; Bolsa Floresta Program; Conservador das Águas Project in Extrema/MG; Water Guardian Program; Ecosystem services in APA da Fazendinha; Quintais Amazônicos Project; BioREC Project – Mamirauá; REDD+ projects in practice and the evolution of voluntary markets; REDD+ opportunities for the Amazon; Carbono RECA Project). They were presented and discussed at the Amazon Ecosystem Services Experiences Seminar (online), held between March 23 and 26, 2021. PES projects are consolidated as important instruments to support the recovery and conservation of natural areas, and can contribute, in a transitional way, to other sustainable development initiatives in the Amazon. In deforested regions, crop converted lands, and regions under pressure of illegal deforestation, PES can support reforestation initiatives, combined or not with production systems, for the purposes of biodiversity conservation, carbon sequestration and water supply. Combining nature conservation through PES with sustainable production systems (Agroforestry, Forestry and Non-Timber Forest Products Management, Fisheries management and aquaculture, Regenerative Agriculture, Agroecological Livestock, among others) presents itself as a good alternative for the sustainability of the Amazon and for their people.